FoxB, a new and highly conserved key factor in arthropod dorsal–ventral (DV) limb patterning - Miriam Heingård; Natascha Turetzek; Nikola-Michael Prpic; Ralf Janssen (EvoDevo, 2019)
Abstract Forkhead box (Fox) transcription factors evolved early in animal evolution and represent important components of conserved gene regulatory networks (GRNs) during animal development. Most of the researches concerning Fox genes, however, are on vertebrates and only a relatively low number of studies investigate Fox gene function in invertebrates. In addition to this shortcoming, the focus of attention is often restricted to a few well-characterized Fox genes such as FoxA (forkhead), FoxC (crocodile) and FoxQ2. Although arthropods represent the largest and most diverse animal group, most other Fox genes have not been investigated in detail, not even in the arthropod model species Drosophila melanogaster. In a general gene expression pattern screen for panarthropod Fox genes including the red flour beetle Tribolium castaneum, the pill millipede Glomeris marginata, the common house spider Parasteatoda tepidariorum, and the velvet worm Euperipatoides kanangrensis, we identified a Fox gene with a highly conserved expression pattern along the ventral ectoderm of arthropod and onychophoran limbs. Functional investigation of FoxB in Parasteatoda reveals a hitherto unrecognized important function of FoxB upstream of wingless (wg) and decapentaplegic (dpp) in the GRN orchestrating dorsal–ventral limb patterning.